Abused children in a Philippine urban setting their profile, social acceptability and aspirations - Amongo, Elena T. (1986)
The author aimed to investigate selected demographic and behavioral characteristics in relation to child abuse. The author also aimed to determine the differences between/among the perceptions of the abused children when they are grouped according to ten variables: sex, age, grade/year level, number of children in the family, highest educational attainments of father/mother, combined annual income of parents/guardians, in-school/out-of-school before institutionalization, type of abuse and number of times abused.
Thesis (M.Ed.)--University of the Philippines, Diliman.
Typescript.
Keywords: Child abuse -- Philippines